Perencanaan Fasilitas Pesepeda pada Jalan Jenderal Ahmad Yani Kota Langsa - Thahirah, Ainaya; Iqbal, Iqbal; Balqis, Putri (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2026)
The increasing need for sustainable transportation drives the importance of providing safe and integrated bicycle facilities in urban road networks. This study analyzes the existing conditions and plans for bicycle facilities on Jalan Jenderal Ahmad Yani, Langsa City, as an effort to improve road user safety and support sustainable mobility. The research methods used include a three-day traffic volume survey during peak hours, road geometric measurements, and road section performance analysis based on the 2023 Indonesian Road Capacity Guidelines (PKJI). The results show that the peak traffic volume reaches 6,424 vehicles/hour on a two-lane, two-way undivided road (2/2 UD) with an effective width of approximately 7.0–7.5 meters. The basic capacity of the road section is 2,800 pcu/hour which after being adjusted for various adjustment factors becomes approximately 2,311 pcu/hour. Traffic volume on each segment ranges from 2,050.4 to 3,833.2 pcu/hour with a saturation degree value between 1.04 and 1.98 and a service level in category F, indicating that traffic flow has exceeded capacity and is operating in unstable conditions. Simulation results of the implementation of bicycle lanes show a decrease in road capacity to around 1,969–2,011 pcu/hour, thus potentially worsening traffic performance. Therefore, the implementation of bicycle lanes on Jalan Jenderal Ahmad Yani is currently not feasible without reorganizing road space and adequate control of side obstacles. The results of this study can be a basis for consideration for the Langsa City Government in planning safe, realistic, and sustainable bicycle facilities.